Strategic Resource Management in Islamic Boarding Schools: The Role of Income-Generating Units in Supporting Educational Goals - Kurniady, Dedy Achmad; Suharto, Nugraha; Suryadi, Suryadi; Hafidh, Zaini; Permana, Riyaldi Dithia (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study explores the role of Income-Generating Units (IGUs) in promoting the economic independence of Islamic boarding schools. This study focuses on the mechanism of IGUs' contribution to the financial and educational sustainability of Islamic boarding schools, considering that the existing literature is still limited in discussing this aspect in depth. The main objective of this study is to investigate the strategies and resources that enable Islamic boarding schools to achieve economic independence to support the sustainability of their education. This study uses a qualitative with case study approach in Islamic boarding schools that have developed various mining, fisheries, and agribusiness businesses. Data were collected through interviews, observations, document reviews, and Focus Group Discussions (FGDs). The data analysis process includes classification, processing, and validation with the help of NVIVO software for effective management and coding of qualitative data. The results show that the economic success of Islamic boarding schools is driven by three main factors: effective resource utilization, strategic partnerships with external parties, and active involvement of students in business activities. This study confirms that IGUs play an important role in ensuring the sustainability of Islamic boarding schools, both in terms of financial independence and the development of student's practical skills, which simultaneously strengthens the competitiveness of Islamic boarding school education.